My promised land : the triumph and tragedy of Israel - Shavit, Ari (Spiegel & Grau, 2013)
"Drawing on historical documents, interviews, and private diaries and letters, as well as his own family's story, My Promised Land is a riveting narrative that is larger than the sum of its parts: both personal and profound historical dimensions. As Ar Shavit examines the complexities and contradictions of the Israeli condition, he asks difficult but important questions: why did Israel come to be? How did it come to be? Can it survive? Culminating with an analysis of the issues and threats that Israel is currently facing."